"LEMKIVSKA VATRA" AS A RESOURCE FOR THE DEVELOPMENT OF ETHNO-EXOGENIC TOURISM IN UKRAINE - SMYRNOV, Ihor; LUBITSEVA, Olga (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2024)
Geographical and historical features of the Lemkis as the mostwestern ethnic group of the Ukrainian people are revealed. The example of the International Ethnographic Festival "Lemkivska Vatra", which is held annually in the small town of Zdynia in the Small Poland Voivodeship of Poland, shows the possibilities of strengthening tourist cooperation between Polish and Ukrainian Lemkis in the current difficult conditions of unmotivated Russian aggression against Ukraine. Starting from 2022, the "Lemkivska Vatra" festival has been consistently running a line in support of Ukraine in this war, which was reflected in its slogan: "Vatra is in solidarity with Ukraine." Linguistic-cultural and geographical-historical features of Lemkivshchyna were analyzed and on this basis the close connection of the Lemkis with Great Ukraine, which they constantly maintained and maintain today under various historical conditions, were emphasized. The activation of tourist connections between Lemkis in Poland and Ukraine will contribute not only to the further expansion of the Ukrainian-speaking space, but also to the strengthening of Ukrainian-Polish relations. Profiles of outstanding representatives of the Lemkos, who have gained worldwide popularity and are therefore interesting for the development of tourism, are presented and characterized. Some of them are well known in Ukraine, moreover, their activities contributed to the formation of the national and patriotic consciousness of the Ukrainian nation. We are talking, first of all, about Mykhailo Verbytskyi, a Lemko by origin, the author of the music for the National Anthem of Ukraine. The next name of Lemko’s origin, which is now known all over the world, is Andy Warhol (Andriy Vargola) - an American of Lemko’s ancestry, who created a whole direction of modern cultural and artistic development called "pop art". Nikifor Drovniak, a representative of the "naive" folk art of the Polish Carpathians, also has Lemko’s roots. Finally, one cannot fail to mention Bohdan-Ihor Antonych, a Ukrainian-Lemko’s poet and writer. All of them have a connection with tourism, since the corresponding attractions and monuments were created both in Ukraine and in other countries (USA, Poland, Slovakia), but, unfortunately, they are not well known. The article fills this gap.